A brief review on behavior of sandstone, limestone and shale rocks under laser radiations - Patel, M.C. (World Academy of Research in Science and Engineering, 2020)
The Laser devices convert one form of energy into photonic energy or photons which are electro-magnetic radiations. This photonic energy in the form of laser radiations has enough potential that rock destruction can be achieved by its interaction with rocks. This paper surveys research and experimentation performed in the past to study laser-rock interactions from the date laser was invented. The paper elaborates about mechanisms of rock destructions due to laser radiation interactions for sandstone, limestone and shale rocks. Laser radiations operate using three basic rock destruction mechanisms as thermal spalling or chipping at low laser power, melting or fusion at high laser power and vaporization at very high laser power for sandstone and shale rocks, whereas for limestone rocks dissociation is the mechanism of rock destruction. The paper also explains utilization of absorbed laser energy for primary processes and secondary effects in the rocks. Â© 2020, World Academy of Research in Science and Engineering. All rights reserved.